Low frequency approximation of mutual modal radiation efficiency of a vibrating rectangular plate - Zawieska, W.M.; Rdzanek, W.P. (Archives of Acoustics, 2014)
This paper presents some elementary formulations for the mutual modal radiation efficiency of a simply supported rectangular plate embedded into a rigid infinite baffle. The magnitude makes it possible to introduce the intermodal plate’s interactions into the total radiation efficiency of the plate vibrating under the influence of an external surface force. The approximate formula has been expressed as a combinations of some trigonometric and special functions. The formula is convenient for some numerical computations of the modal and total radiation efficiency values of the plate.